THE EFFECT OF COMPETENCE AND CAPABILITY ON COMPETITIVE ADVANTAGE - fausiah; Yusuf, Ria Mardiana; Hakim, Haeriah (Journal of Risk and Uncertainty Issues, 2023)
The purpose of this study is to determine the effect of competence and capability on competitive advantage. This research was conducted at the Bira Tourism Cottage (Villa) in Bulukumba Regency. The number of samples taken was 67 villa management in Tanjung Bira Beach, Bulukumba Regency, using the saturated sampling method. Data collection was carried out through questionnaires and interviews. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis it was found that competence has a positive and significant effect on competitive advantage, as well as capabilities have a positive and significant effect on competitive advantage. This proves that if the company's resources, such as competencies and capabilities, are managed properly and have a competitive advantage, they can improve company performance.